Perspective of Women in the Nepalese Economy: Opportunities, Challenges and Future Scope (Economic Journal of Nepal, 2019)
Bidirectional relationship between economic development and women's empowerment is one of the issues in this relationship. Economic growth and prosperity is necessary to improve gender inequality by reducing poverty. Another argument assumes that women could play a fundamental role in development. Thus, equality is valuable. Capacity of women is crucial for changing their live positively. This paper explores the scopes, and opportunities provided by the government policies for Nepalese women and analyzed the constraints in implementing the policies based on this authors' two previous studies -- Effectiveness of Gender Responsive Budgeting in Nepal, 2019; and Women's Contribution in Family Economy in Nepal, 2010. Although more than NRs 500 billion of budget is allocated in the programs directly benefitting women, results are not observed as expected. Sustainable economic development is possible only if the women are capable to utilize the resources; capable to control and reap the benefits of economic opportunities; and capable to make strategic decision for changing their lives positively, once they have access to the resources. Once women are capable, there would be no limitation to be involved in economics. Result Based Budgeting (RBB) systems has proven to be a compatible framework for the institutionalization of gender budgeting.